Novos cenários para treinamento em radiologia oral: desempenho clínico e percepção de estudantes de graduação sobre modelos de impressão 3D - Mello, Wislem Miranda de (2024)
Introduction: Intraoral radiographic techniques teaching is fundamental in the training of dental surgeons. To avoid biological risks associated with X-rays exposure, training must be carried out on specific phantoms. However, the commercial phantoms available for training in Oral Radiology are expensive and represent only a standard patient type, without anatomical variations or pathological changes, which does not reflect the diversity in clinical practice. The use of 3D printing to build training models appears as a viable alternative to traditional mannequins. However, it is necessary to evaluate the impact of 3D printing on the teaching-learning process of intraoral radiographic techniques. Objective: To evaluate the impact of 3D printed models on the teaching and learning process of undergraduate students in intraoral radiographic techniques. Methodology: Two 3D printed training models were developed: a traditional model simulating a standard adult patient and a customized model with pathological and physiological changes (impacted third molar and edentulous region). The students underwent pre-clinical training divided into a control group (CG, n = 23), which had access to the traditional model, and a test group (TG, n = 20), which had access to both models. Afterwards, they performed a complete examination of bitewing and periapical radiographs on patients and completed a perception questionnaire. The radiographs were evaluated for technical parameters. Descriptive statistics and the Mann-Whitney test were used to compare the groups. Results: Students provided positive feedback regarding the use of 3D printing. The TG reported a more realistic training experience than the CG (p = 0.037). Both groups demonstrated good clinical performance (CG = 7.41; GT = 7.52) and no significant differences were observed between them. Conclusions: 3D printing technology is an interesting option for manufacturing simulators for pre-clinical training in Oral Radiology, as it allows the creation of 3D printed models with radiographic image projection suitable for training, good clinical performance, reduces student stress, and increases confidence during clinical care. Additionally, 3D printing enables the creation of new preclinical training scenarios that more realistically replicate the clinical environment.